The Coronary Artery Calcium Score as Prognostic Tool for Cardiovascular Events in Patients with Cushing’s Syndrome - van Baal, Lukas; Lehmann, Nils; Jöckel, Karl-Heinz; Erbel, Raimund; Umutlu, Lale; Schlosser, Thomas; Führer, Dagmar; Unger, Nicole (Hormone and Metabolic Research, 2025)
Cushing’s syndrome (CS) is associated with high morbidity and mortality triggered by increased risk for cardiovascular events. Nevertheless, no screening tool to predict the individual risk for these events in patients with Cushing’s syndrome has been established. Nonenhanced electron-beam computed tomography scans with calculation of the Coronary Artery Calcium (CAC) score may offer a non-invasive method. Hence, we evaluated the diagnostic accuracy of Agatston score to predict the risk of a cardiac event in patients with Cushing’s syndrome. Single center prospective study of 34 patients with endogenous CS Multidetector computer tomography and calculation of CAC score was performed at diagnosis of CS. Prevalence of cardiovascular events was documented with median follow-up over 5 years and results were compared with data from the Heinz Nixdorf Recall (HNR) Study. In addition, correlations of CAC score with parameters of cortisol excess were evaluated. CAC score was significantly higher in CS patients with a cardiovascular event than in patients without an event (117 vs. 90; p=<0.01). An odds ratio of 31.7 (p=0.03, 95% CI: 1.3–773.0) for a cardiovascular event could be shown in Cushing’s syndrome patients with a CAC score>75th risk factor-specific reference percentile, while the odds ratio in the HNR study was 4.5 (p<0.01, 95% CI: 3.0–6.9). No correlation between the degree of cortisol excess and CAC score was evident. The CAC score>75th risk factor-specific reference percentile could offer a useful screening tool to precise the cardiovascular risk in patients with Cushing’s syndrome.
Keywords: adrenal; hypercortisolism; coronary artery calcium; coronary artery disease; electron-beam computed tomography